The Expression of Markers for Intratubular Germ Cell Neoplasia in Normal Infantile Testes - Kvist, Kolja; Clasen-Linde, Erik; Langballe, Oline; Hansen, Steen Holger; Cortes, Dina; Thorup, Jorgen (Frontiers in Endocrinology, 2018)
Background: Positive immunohistochemical expression of testicular cancer markers is often reported beyond 12 months of age in cryptorchid testes, which is assumed to indicate delayed maturation of the fetal germ cells, or neoplastic changes. These findings allowed for questions as to the extent of positive reaction in normal testes. The aim of the study was to clarify the expression of these markers in a normal material up to 2 years. Methods: Testicular material from 69 boys, ages 1–690 days, who died of causes with no association of testicular pathology. Histology sections were incubated with primary antibodies including anti-placental-like alkaline-phosphatase (PLAP), anti-C-Kit, anti-D2-40 and anti-Oct3/4. The mean germ cell number per tubular transverse section (G/T) was calculated based on the G/T of both testes of every boy. Results: The mean G/T declined through the 690 days. PLAP appeared stably expressed throughout the ages studied. The likelihood of a positive reaction for C-Kit waned with increasing age within the study period. Positive staining for D2-40 and Oct3/4 was demonstrated up to 6 and 9 months respectively. Conclusion: Up to one or two years of age, normal infantile testes contain germ cells positive for the immunohistochemical markers commonly utilized to aid in the detection of testicular cancer. This finding supports the concept of germ cells undergoing a continuous maturational process in a heterogeneous fashion, and that this process is not complete by two years of age.